THE INTERRELATION OF LOGIC AND ETHICS IN WITTGENSTEIN’S PHILOSOPHY: FROM LANGUAGE STRUCTURES TO EVERYDAY LIFE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article presents a theoretical analysis of the relationship between ethical and logical thinking in the philosophical legacy of Ludwig Wittgenstein. The study comparatively examines Wittgenstein’s early work, Tractatus Logico-Philosophicus, and his later work, Philosophical Investigations, in order to reveal the internal connection between his system of logical reasoning and his reflections on ethical issues. The article also explores how ethical values manifest within the limits of human language and logical thought, as well as the influence of these ideas on twentieth-century philosophical discourse. According to Wittgenstein, ethical meaning cannot be expressed directly but appears indirectly through the logical structure of language, playing an important role in understanding the spiritual dimension of human life. Furthermore, the study analyzes the significance of this perspective in the history of philosophy and examines its relevance for contemporary ethical theory and logical methodology.